2022
DOI: 10.3390/app12020585
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Kinetics and Kinematics in Runners with Patellofemoral Pain: A Retrospective Case–Control Study Using Musculoskeletal Simulation

Abstract: Patellofemoral pain (PFP) is a common atraumatic knee pathology in runners, with a complex multifactorial aetiology influenced by sex differences. This retrospective case–control study therefore aimed to evaluate lower limb kinetics and kinematics in symptomatic and control male and female runners using musculoskeletal simulation. Lower extremity biomechanics were assessed in 40 runners with PFP (15 females and 25 males) and 40 controls (15 females and 25 males), whilst running at a self-selected velocity. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Cut-off frequencies were optimized using residual analysis for both kinetic and kinematics data [ 43 ]. The velocity of walking (m/s) was calculated as mean linear velocity of the model centre of mass in the anterior direction during the stance phase using Visual 3D [ 44 ]. Stride length (m) was determined as the linear anterior distance in the foot centre of mass location at footstrike between initial and subsequent ipsilateral footfalls [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cut-off frequencies were optimized using residual analysis for both kinetic and kinematics data [ 43 ]. The velocity of walking (m/s) was calculated as mean linear velocity of the model centre of mass in the anterior direction during the stance phase using Visual 3D [ 44 ]. Stride length (m) was determined as the linear anterior distance in the foot centre of mass location at footstrike between initial and subsequent ipsilateral footfalls [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each biomechanical and cartilage failure outcome variable; means, standard deviations (SD) and 95% confidence intervals (95% CI) around the mean were calculated. To compare participant characteristics, biomechanical and cartilage failure outcomes between healthy weight and obese groups, between groups linear mixed effects models were adopted using the restricted maximum-likelihood method, with group (i.e., obese/healthy weight) included as a fixed factor and random intercepts modelled by participants [ 44 ]. Linear regression analysis was also adopted in both groups to determine the relationship between BMI and peak force, peak stress and peak strain.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the probability of stress fracture for each participant in each footwear condition firstly by accounting for the daily running distance, which was included in the model as runners completing 5.0 km/day for 100 consecutive days [25,26,41]. The number of loading cycles/footfalls per day in each footwear condition was quantified by dividing the modelled daily running distance by the step length in each footwear outlined in the aforementioned running biomechanics section [45].…”
Section: Probabilistic Stress Fracture Modelmentioning
confidence: 99%
“…Previous analyses have shown that those suffering from patellofemoral pain exhibit reduced knee joint range of motion as a compensatory strategy to decrease knee loading and reduce pain during sports movements [39,40]. This is an undesirable mechanism in active individuals, as it negatively affects the ability to perform functional sports movements effectively, making reductions in pain particularly important in this population from the standpoint of biomechanical function.…”
Section: Knee Biomechanicsmentioning
confidence: 99%